Prediction of the median IDA curve by employing a limited number of ground motion records. - Azarbakht, Alireza (Earthquake engineering & structural dynamics.)
A methodology has been proposed which can be used to reduce the number of ground motion records needed for the reliable prediction of the median seismic response of structures by means of incremental dynamic analysis (IDA). This methodology is presently limited to predictions of the median IDA curve only. The reduction in the number of ground motion records needed to predict the median IDA curve is achieved by introducing a precedence list of ground motion records. The determination of such a list is an optimization problem, which is solved in the paper by means of (1) a genetic algorithm and (2) a proposed simple procedure. The seismic response of a simple, computationally non-demanding structural model has been used as input data for the optimization problem. The presented example is a three-storey-reinforced concrete building, subjected to two sets of ground motion records, one a free-field set and the other a near-field set. It is shown that the median IDA curves can be predicted with acceptable accuracy by employing only four ground motion records instead of the 24 or 30 records, which are the total number of ground motion records for the free-field and near-field sets, respectively.